2018
DOI: 10.22452/mojem.vol6no1.4
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Thinking And Strategic Leadership For Change: Lessons For Technical Universities In Ghana

Abstract: Global competition is forcing tertiary institutions to excel in knowledge-creation that are relevant and innovative. Innovations bring solutions to societal problems. Perhaps a new system of thinking will enhance the relevance and sustainability of Ghana's new Technical Universities (TU) that were established by PNDC Law 321 to provide technical leadership, entrepreneurial solutions, and support of industries for its national development. For strategic thinking, the TUs are advised to avoid the Polytechnic tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 5 publications
0
13
0
1
Order By: Relevance
“…A study conducted by [1] found that strategic leadership influences activities and the thinking behind ideas in order to 'move people' to accomplish change. For example; one the institutional leader's echoed through interview that to lead strategically, "Institutional leaders must lead academically … and in solving social problems … leave those politicians … [if ] they [politicians] create problems, ….…”
Section: Strategic Thinking: the Conceptmentioning
confidence: 99%
See 4 more Smart Citations
“…A study conducted by [1] found that strategic leadership influences activities and the thinking behind ideas in order to 'move people' to accomplish change. For example; one the institutional leader's echoed through interview that to lead strategically, "Institutional leaders must lead academically … and in solving social problems … leave those politicians … [if ] they [politicians] create problems, ….…”
Section: Strategic Thinking: the Conceptmentioning
confidence: 99%
“…First of all, every vision must be shared, communicated, and spread with a passion that becomes contagious [22]. It was evident in their study [1] that institutional leadership in African universities has to think of ways to demonstrate passion and commitment to a dream for others to believe and yield to any systematic change. Whereby strategic change can only take place when people are ready and looking forward to a better alternative [24].…”
Section: Strategic Thinking: the Conceptmentioning
confidence: 99%
See 3 more Smart Citations